The effects of quercus infectoria gall extract on the morphology of gram-positive bacteria, gram-negative bacteria and yeast - Rahman, Norhaswani Abd (Universiti Sains Malaysia, 2014)
The gall extract from Q. infectoria is well known to have a broad spectrum of activity against Gram-positive bacteria, Gram-negative bacteria and yeast. However, studies on identifying and comparing the antimicrobial mechanisms of phytochemicals in the Q. infectoria gall extract are still limited and not well established. The aims of this study were to determine the antimicrobial activity of methanolic 0. infectoria gall extract against Gram-positive, Gram-negative and yeast strains, and also to study the effects of the gall extract on the cell morphology of the tested strains. Antimicrobial activity of gall extract was screened using disc diffusion method against Gram-positive bacteria (S. agalactiae), Gram-negative bacteria (P. vulgaris) and yeast (C. albicans). Minimum inhibitory concentration (MIC) was determined using twofold serial microdilution technique at concentrations ranging between 0.01 mg/mL and 5.00 mg/mL (for bacteria) and between 0.02 mg/ml and 12.00 mg/ml (for yeast). Minimum bactericidal concentration (MBC) and minimum fungicidal concentration (MFC) were determined by subculturing the wells plate which showed no apparent growth or turbidity onto the agar plates. Morphological changes of treated cells (IxMlC and 4xMIC) were then observed under scanning electron microscope (SEM). A higher antimicrobial activity was observed against C. albicans in this study. Based on the MBC to MIC ratio or MFC to MIC ratio, the extract was considered as bactericidal and fungicidal against the tested strains. Morphological changes were observed in all treated cells but more distinct at 4xMIC under SEM. This preliminary study provides scientific information to the effect of gall extract on the bacterial and fungal morphology suggesting its antimicrobial mechanism on the cell wall and membrane integrities.